2012
DOI: 10.1042/bj20111871
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/calmodulin inhibition of the Arabidopsis BRASSINOSTEROID-INSENSITIVE 1 receptor kinase provides a possible link between calcium and brassinosteroid signalling

Abstract: The receptor kinase BRI1 (BRASSINOSTEROID-INSENSITIVE 1) is a key component in BR (brassinosteroid) perception and signal transduction, and has a broad impact on plant growth and development. In the present study, we demonstrate that Arabidopsis CaM (calmodulin) binds to the recombinant cytoplasmic domain of BRI1 in a Ca2+-dependent manner in vitro. In silico analysis predicted binding to Helix E of the BRI1 kinase subdomain VIa and a synthetic peptide based on this sequence interacted with Ca2+/CaM. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
54
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 46 publications
3
54
1
1
Order By: Relevance
“…The exciting work of Oh et al (2012) also demonstrated that coexpression of CaM with the cytosolic kinase domain of BRI1 in a heterologous system (E. coli) resulted in an impairment of BRI1 autophosphorylation and transphosphorylation (in this case, of E. coli proteins). This work raises the intriguing possibility that elevation of cytosolic Ca 2+ might act, through Ca…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations
“…The exciting work of Oh et al (2012) also demonstrated that coexpression of CaM with the cytosolic kinase domain of BRI1 in a heterologous system (E. coli) resulted in an impairment of BRI1 autophosphorylation and transphosphorylation (in this case, of E. coli proteins). This work raises the intriguing possibility that elevation of cytosolic Ca 2+ might act, through Ca…”
Section: +mentioning
confidence: 99%
“…However, a recent report has demonstrated a physical and functional interaction between BRI1 and the Ca 2+ -binding protein CaM. Oh et al (2012) have shown that Arabidopsis CaM7 displays Ca…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…-mediated signals could regulate a broad range of physiological activities related to plant growth, development, and responses to environmental stimuli (Zhang et al, 2002;Vanoosthuyse et al, 2003;Charpenteau et al, 2004;Hua et al, 2004;Liu et al, 2008;Kim et al, 2009a;Yang et al, 2010;Oh et al, 2012). Among all these CaM-regulated kinases, CCaMK has been widely studied because of its role in symbioses, developmental processes, and stress responses.…”
Section: +mentioning
confidence: 99%
“…Some RLKs from plants contain only a kinase domain and thus are named receptor-like cytoplasmic kinases. Some receptor-like cytoplasmic kinases, such as CRCK1 and homologs (Yang et al, 2004), and RLKs, such as SRK, CaM-binding receptor-like kinase, AtCaMRLK, AtCRLK1, and BRI1, are CaM-binding proteins (Vanoosthuyse et al, 2003;Charpenteau et al, 2004;Kim et al, 2009a;DeFalco et al, 2010b;Yang et al, 2010;Oh et al, 2012). Last but not least, some of the mitogen-activated protein kinases (MAPKs), specifically members of Moon et al (2005) subgroup D of MAPK in Arabidopsis and rice (Oryza sativa), were reported to be regulated by Ca 2+ /CaM (Ding et al, 2009;Takahashi et al, 2011).…”
mentioning
confidence: 99%